Madrasah Funding Management: Case Study at MTs Muhammadiyah Wates Kulon Progo (Manajemen Pendanaan Madrasah: Studi Kasus di MTs Muhammadiyah Wates Kulon Progo) - Nonci, Riswan D; Adilla, Bekti Faizah; Munastiwi, Erni (Shautut Tarbiyah, 2024)
This article written to review and analyse about funding managemen in the Islamic Middle School (Madrasa) level. This research was conducted in a non-profit Islamic Secondary School, Madrasah Tsanawiyah Muhammadiyah Wates (MTs Muh Wates) by qualitative approach and descriptively explained. Data acquisition was carried out by interviews, observations, and documentation. At the research site, educational funds are obtained from at least two sources, there are School Operational Assistance / Bantuan Operasional Sekolah (BOS) obtained from National Revenue and Expenditure Budget / Anggaran Pendapatan dan Belanja Negara (APBN) funds and committee donations from student’s parents. All these funds are accumulated and allocated on costs needed for the necessary expenses to facilitate teaching and learning activities in the school. Keywords: Madrasah Funding Management, School Operational Assistance